2015
DOI: 10.1097/tp.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Alone in End-Stage Renal Disease Patients With Hepatitis B Liver Cirrhosis

Abstract: Kidney transplantation alone may be safe in patients with compensated hepatitis B virus LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…A recent single center study provided data of an excellent five-year survival rate (94%) in 12 cirrhotic patients with hepatitis B after kidney transplantation alone[ 16 ].…”
Section: Hbv Evaluation In the Pretransplantation Settingmentioning
confidence: 99%
“…A recent single center study provided data of an excellent five-year survival rate (94%) in 12 cirrhotic patients with hepatitis B after kidney transplantation alone[ 16 ].…”
Section: Hbv Evaluation In the Pretransplantation Settingmentioning
confidence: 99%
“…Compensated liver cirrhosis secondary to HBV, on the other hand, is not necessarily a contraindication to kidney transplantation alone, in the current era of pre‐emptive or prophylactic antiviral therapy. A recent single‐centre Korean study reported good outcome of kidney transplantation alone in 12 patients (8 with Child‐Pugh class A and 4 with class B) between 1997 and 2011. Liver function worsened in only one of these patients and hepatocellular carcinoma was diagnosed in four patients after a median period of 35 months.…”
Section: Evaluation Selection and Preparation Of The Potential Trmentioning
confidence: 99%
“…Liver function worsened in only one of these patients and hepatocellular carcinoma was diagnosed in four patients after a median period of 35 months. Five‐year patient survival was 100% . However, kidney transplantation alone should not be recommended for HBV patients with decompensated cirrhosis, or those with compensated cirrhosis and portal hypertension.…”
Section: Evaluation Selection and Preparation Of The Potential Trmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed, in a recent study of HCV kidney transplant recipients, that kidney transplantation alone in patients with compensated cirrhosis is problematic when considering their 5‐ and 10‐year survival at 71% (personal data) and 16.4% . This latter result may be explained by the fact that the risk of hepatocellular carcinoma and liver decompensation remains significant and could even be increased by immunosuppressive regimen . Thus, strict screening of hepatocellular carcinoma and evaluation of liver function are crucial in kidney recipients with compensated cirrhosis .…”
mentioning
confidence: 99%